The right to reparations in the context of transitional justice : lessons for Burundi from South Africa, Chile, Peru and Colombia - Fernandez, Lovell (University of Pretoria, 2012)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2011.